Impact of Ionic Composition of Cryoprotective Medium and Cryopreservation on Human Erythrocyte Sensitivity to Mechanical Stress - Aleksandrova, Daria I.; Zemlianskykh, Nina G. (Problems of Cryobiology and Cryomedicine, 2019)
In this research, we have studied the impact of electrolytes and Ca2+ ions on the development of hemolytic damages in human erythrocytes in cryoprotectant solutions under mechanical stress, as well as the eï¬€ect of freeze-thawing of cells in the presence of glycerol and polyethylene glycol (PEG) on their mechanical stability. The decrease in mechanical stability of cells was found when the salt concentration in extracellular medium increased. At the same time, the absence of electrolytes in cryoprotectant solutions reduced their stability under mechanical stress as well. The Ca2+ introduction into the media increased the cell hemolysis only in the presence of PEG, but not glycerol, apparently due to diï¬€ erent eï¬€ects of these substances on the activity of Ca2+-regulating systems. The introduction of salt of ethylenediaminetetraacetic acid (EDTA) into the media composition reduced the erythrocyte membrane mechanical stability in the presence of the both cryoprotectants, which might be due to the chelator eï¬€ect on membrane-bound Ca2+. Cryopreservation of erythrocytes increased their sensitivity to mechanical stress, and even the cryoprotectant removal could not restore the cell properties up to the control parameters. Â  Probl Cryobiol Cryomed 2019; 29(4):Â 317-331